Thermal management of pin-fin heat sinks in square vented cavity using Magnetohydrodynamic hybrid nanofluids under thermal radiation - Daiz, Abdelhak; Hidki, Rachid; Öztop, Hakan Fehmi; Charqui, Zouhair (Pergamon-Elsevier Science Ltd, 2025)
Computational analysis of thermal management of pin-fin heat sinks in square vented cavity by using Magnetohydrodynamics (MHD) hybrid nanofluids under thermal radiation has been performed. The novelty of this work lies in the separation of the heat-generating blocks and the nanofluid by a thermally conductive and electrically insulating strip, since the electronic components need to be isolated from water (base fluid). Finite Element Method (FEM) was used to solve governing equations of flow and temperature. Studied parameters are Reynolds numbers (100 <= Re <= 1000), Richardson numbers (0 . 01 <= Ri <= 100), Hartmann number (0 <= Ha <= 100), thermal conductivity ratio (0 . 1 <= Ks <= 100), thermal radiation parmeter (Rd = 0, 0.4 and 0.8) and volume fraction of hybrid nanoprticles (0% <= phi <= 5%). The main results show that increasing Reynolds number from 100 to 1000 leds to a decrease in the average temperature of 80.24 % for Ri = 100. Furthermore, the presence of the magnetic field reduces the average temperature by 22 % when Ha increases from 0 to 100 for high vlaues of Re . On the other hand, numerical simulations show that the addition of 5 % hybrid nanoparticles contributes to a 7.42 % increase in the average temperature compared to the base fluid (0 % nanoparticles) for Re = 1000.
Keywords: Thermal management; Radiation; Magnetic field; Cavity; Hybrid nanofluids; Heat sink